Addressing Challenges to access to Justice for Victims of Medical Malpractice in Nigeria - Onomrerhinor, Flora Alohan; Jubril, Adejumo Omobolaji (NIU Journal of Legal Studies, 2026)
Medical malpractice litigation provides an avenue for victims of malpractice to get justice and restore confidence in the health care system. However, a close examination of medical malpractice litigation in Nigeria reveals some challenges to the country’s justice delivery. Although substantive law on medical negligence is relatively well developed, the practical ability of patients to pursue claims is limited due to procedural challenges. The financial burden associated with expert reports and the absence of structured compensation mechanisms leaves many injured patients without redress. This paper examines how these challenges can be surmounted. It adopts an analytical legal research approach. It reviews extant literature on the subject and compares the Nigerian situation with jurisdictions like the United Kingdom and South Africa. It finds the Nigerian system for financing medical negligence claims inadequate. Claimants bear nearly all initial costs, especially the procurement of medical expert reports which are often expensive due to limited availability and professional reluctance to testify. legal aid offers almost no support for tort-based medical claims. Professional indemnity insurance, although encouraged, is not mandatory and sparsely implemented among private hospitals and individual practitioners. Comparative insights reveal that countries with conditional fee arrangements, state-backed insurance schemes and statutory compensation funds experience fewer access barriers. It concludes that the present financial architecture for medical malpractice litigation in Nigeria is inadequate and constitutes significant barrier to access to justice and recommends a combination of legislative and policy reforms such as compulsory malpractice insurance, establishment of statutory compensation fund and regulated third-party funding.  Keywords: Access, Funding, Justice, Malpractice Negligence, Third party.